The Communication Anxiety Instrument for Elementary School Children: Validity and Reliability Instruments - Hidayati, Richma; Fajrie, Nur; Mohamed Nor Azhari bin Azman (Universitas Pendidikan Ganesha, 2025)
Communication anxiety is a significant challenge among elementary school students, especially following changes in interaction patterns due to technological advancements and the COVID-19 pandemic. This condition can hinder children's social and emotional development if not detected and addressed early. This study aims to analyze the validity and reliability of a communication anxiety instrument for elementary school students as a foundation for designing appropriate educational services and interventions. This research employed a quantitative approach with an instrument validation study design. The research subjects were elementary school students selected through purposive sampling, who also served as the instrument trial participants. Data collection methods included questionnaires, documentation, and literature review, using a communication anxiety questionnaire as the research instrument. Data analysis involved Pearson Product Moment validity testing and Cronbach's Alpha reliability testing. The results showed that all 14 instrument items had correlation values greater than 0.361, indicating that they were valid. Furthermore, the Cronbach's Alpha value of 0.886 indicated high reliability. Therefore, the instrument is suitable for identifying levels of communication anxiety among elementary school students. These findings highlight the importance of early detection of communication anxiety to support children's social-emotional development. The implication of this study suggests that a valid and reliable instrument can assist teachers, counselors, and parents in designing more effective communication intervention programs.